Gender Differences Across the Earnings Distribution : Evidence from NLS:86 & HSB:92 - Spyros Konstantopoulos; Amelie F. Constant (Institute for the Study of Labor (IZA), 2004)
This study examines gender differences in the earnings of young adults in the 1980s and 1990s. We determine changes in the gender gap over time in the middle, the tails, and the variability of the earnings distribution. We employ data from two longitudinal, nationally probability samples of high school seniors: the National Longitudinal Study of high school seniors in 1972, and the High School and Beyond Study in 1980 (and the 5th and 4th followup studies respectively). We compute the average differences using effect size estimates expressed in standard deviation units. Differences in the tails and the variability are computed using number and variance ratios respectively. Adjusting for employment selection our findings reveal that once education, occupation, and marital status are taken into account gender differences in earnings (in the middle, the tails, and the variance of the earnings distribution) are eliminated. We observe similar results in gender differences for Whites, Blacks, and Hispanics.
Keywords: J16; C10; J31; 330; gender differences in earnings; general statistical methods; Lohndifferenzierung; Geschlecht; Frauenarbeitslohn; Schätzung; Vereinigte Staaten